Primary neuroendocrine carcinoma of the kidney - Dvorackova, Jana; Macak, Jirka; Brzula, Petr; Tomanova, Radoslava; Dokulil, Jiri (Biomedical papers, 2013)
Background: The objective of the study was to report a rare case of primary neuroendocrine carcinoma of the right kidney in a 36 year old male.Methods: The patient was clinically assessed; CT and OctreoScan scintigraphy were performed and levels of 5-HIAA, vanillylmandelic acid and NSE were determined. The tumor and metastases were histologically and immunohistochemically examined.Results: The imaging methods showed a cystic tumor in the lower pole of the right kidney. Macroscopically, the entire tumor was sized 8x8x7 cm. Histologically, it was made up of ribbon-line or trabecular patterns of tumor cells. Occasional adenomatoid and cystic structures were present. The tumor cell nuclei were round or oval, with no irregularities and fine lumpy chromatin. The mitotic count was < 1 /10HPF and the proliferation marker Ki-67 was < 1 % of tumor cells. Immunohistochemically, the tumor cells were positive with antibodies against chromogranin A, synaptophysin, CD56 (focally), cytokeratins AE1-AE3 (focally), vimentin (most cells), glucagon (focally), and pancreatic polypeptide (PP; focally). Antibodies against serotonin, somatostatin, gastrin, vasoactive intestinal polypeptide (VIP) and calcitonin did not react with the tumor. The results of biochemical markers (5-HIAA, vanillylmandelic acid and NSE) did not correlate with development or treatment of the tumor.Conclusions: Primary neuroendocrine carcinoma of the kidney was diagnosed both histologically and immunohistochemically. The patient was clinically investigated using CT and OctreoScan scintigraphy. Within two years from nephrectomy, metastases were found in the right humerus and retrocaval lymph nodes. The metastatic lesions were surgically removed. Currently, the patient's condition is good, with no tumor progression detected.
Keywords: kidney neoplasm; neuroendocrine tumor; carcinoid